2020
DOI: 10.1007/s11869-020-00893-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental pollution and COVID-19 outbreak: insights from Germany

Abstract: The impact of environmental pollutants and climate indicators on the outbreak of COVID-19 has gained considerable attention in the recent literature. However, specific investigation of industrial economies like Germany is not available. This provides us motivation to examine the association between environmental pollutants, climate indicators and the COVID-19 cases, recoveries, and deaths in Germany using daily data from February 24, 2020, to July 02, 2020. The correlation analysis and wavelet transform cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 50 publications
3
38
0
6
Order By: Relevance
“…In Ecuador, concentrations of NO2 and PM2.5 reduced significantly since introduction of lockdown, but O3 concentrations have grown (Zambrano-Monserrate and Ruano 2020). A study (Bilal et al 2020) found that PM2.5, O3, and NO2 have a significant relationship with cases of COVID-19 in Germany.…”
Section: Other Countriesmentioning
confidence: 99%
“…In Ecuador, concentrations of NO2 and PM2.5 reduced significantly since introduction of lockdown, but O3 concentrations have grown (Zambrano-Monserrate and Ruano 2020). A study (Bilal et al 2020) found that PM2.5, O3, and NO2 have a significant relationship with cases of COVID-19 in Germany.…”
Section: Other Countriesmentioning
confidence: 99%
“…In comparison to other pollutants, fine particles generally cause several chronic diseases as they can penetrate deeper into the respiratory system. Furthermore, environmental pollution 25,26,48 contributes to 3 million deaths each year and is ranked among ten risk factors which most contribute to the global burden of disease, [27][28][29] this risk can only be reduced if emerging economies like the South American continent introduce environmental and institutional reforms to reduce the greenhouse gas (GHG) emissions. 30,31,49 Air pollutants are a key risk factor, considered critical respiratory and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The dangerous aspect is its fast-human to human transmission rate. Epidemiology of this novel disease is mainly affected by three factors, i.e., the host, transmission media, and the environment (Bilal et al 2020;Sobral et al 2020).…”
Section: Introductionmentioning
confidence: 99%